Polyamines delay leaf maturation in low‐alkaloid tobacco varieties. (31st July 2018) - Nölke, Greta; Volke, Daniel; Chudobová, Ivana; Houdelet, Marcel; Lusso, Marcos; Frederick, Jesse; Adams, Andrew; Kudithipudi, Chengalrayan; Warek, Ujwala; Strickland, James A.; Xu, Dongmei; Schinkel, Helga; et al.
Abstract: The development of low‐alkaloid (LA) tobacco varieties is an important target in the tobacco breeding industry. However, LA Burley 21 plants, in which the Nic1 and Nic2 loci controlling nicotine biosynthesis are deleted, are characterized by impaired leaf maturation that leads to poor leaf quality before and after curing. Polyamines are involved in key developmental, physiological, and metabolic processes in plants, and act as anti‐senescence and anti‐ripening regulators. We investigated the role of polyamines in tobacco leaf maturation by analyzing the free and conjugated polyamine fractions in the leaves and roots of four Burley 21 varieties: NA (normal alkaloid levels, wild‐type control), HI (high intermediates, nic2 − ), LI (low intermediates, nic1 − ), and LA ( nic1 − nic2 − ). The pool of conjugated polyamines increased with plant age in the roots and leaves of all four varieties, but the levels of free and conjugated putrescine and spermidine were higher in the LI and LA plants than NA controls. The increase in the polyamine content correlated with delayed maturation and senescence, i.e., LA plants with the highest polyamine levels showed the most severe impaired leaf maturation phenotype, characterized by higher chlorophyll content and more mesophyll cells per unit leaf area. Treatment of LA plants with inhibitors of polyamine biosynthesis and/or the growth regulator Ethephon ® reduced accumulation of polyamines, achieving a partial amelioration of the LA phenotype. Our data show that the regulation of polyamine homeostasis is strongly disrupted in LA plants, and that free and conjugated polyamines contribute to the observed impairment of leaf maturation.